2022
DOI: 10.1186/s12943-022-01658-x
|View full text |Cite
|
Sign up to set email alerts
|

CREB3L1 promotes tumor growth and metastasis of anaplastic thyroid carcinoma by remodeling the tumor microenvironment

Abstract: Anaplastic thyroid carcinoma (ATC) is an extremely malignant type of endocrine cancer frequently accompanied by extrathyroidal extension or metastasis through mechanisms that remain elusive. We screened for the CREB3 transcription-factor family in a large cohort, consisting of four microarray datasets. This revealed that CREB3L1 was specifically up regulated in ATC tissues and negatively associated with overall survival of patients with thyroid cancer. Consistently, high expression of CREB3L1 was negatively co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 51 publications
1
36
0
Order By: Relevance
“…In contrast, IRF9 , a TF involved in immune response regulation, was primarily found in iCAF, 50 while MEF2C , influencing myogenesis and angiogenesis, was mostly present in myCAF 51 . Lastly, CREB3L1 , a TF that regulates collagen formation, 52 was uniquely expressed in matCAF (Figure 3F). Interestingly, similar patterns were noted in other cancer types such as BRCA and LUAD, where the active TF regulatory networks of diverse CAF subtypes likewise demonstrated significant functional distinctions (Figure S7B,C).…”
Section: Resultsmentioning
confidence: 98%
“…In contrast, IRF9 , a TF involved in immune response regulation, was primarily found in iCAF, 50 while MEF2C , influencing myogenesis and angiogenesis, was mostly present in myCAF 51 . Lastly, CREB3L1 , a TF that regulates collagen formation, 52 was uniquely expressed in matCAF (Figure 3F). Interestingly, similar patterns were noted in other cancer types such as BRCA and LUAD, where the active TF regulatory networks of diverse CAF subtypes likewise demonstrated significant functional distinctions (Figure S7B,C).…”
Section: Resultsmentioning
confidence: 98%
“…The dataset details are explained in Table 1. The possible batch effect among datasets was removed using the function of removeBatchEffect in the Limma package version 3.54 in the R 4.2.2 environment [10,[17][18][19][20][21]. The data was also quantile normalized.…”
Section: Gene Expression Datasets and Preprocessingmentioning
confidence: 99%
“…In COAD, we observed that NFIX [54], a TF regulating cell proliferation, was mainly expressed in proCAF. Meanwhile, as a member of TFs regulating immune response, IRF9 was predominantly expressed in iCAF [55]; while MEF2C, a TF regulating myogenesis and angiogenesis [56], was overwhelmingly expressed in myCAF; and CREB3L1, a TF regulating collagen formation [57], was exclusively expressed in matCAF (Fig. 3F).…”
Section: Diverse Activated Transcription Factor Of Caf Subtypesmentioning
confidence: 99%